Análisis comparativo del delito de trata de personas en la legislación penal ecuatoriana. - Muenala Morales, Carlos Waldemar (2015)
This paper aims primarily to provide a comparative analysis of the crime of trafficking in Ecuador's criminal law, seeking first historical, legal and doctrinal one of the oldest crimes of the preceding history of mankind. Referencing the Constitution, international treaties and the new Code of Criminal Integral (COIP) and other Ecuadorian law, a legal analysis of the evolution of this crime in our country will be held especially in the province of Imbabura, to know what it is the State's commitment in the fight against this crime that has taken hold in recent years in Ecuador and Latin America. In the present study will be necessary to make use of comparative law, analyzing similarities and differences about the treatment given to the crime of trafficking in other countries. Using a practical case in the Canton province of Imbabura Ibarra will; analyzing step by step the procedure to be followed before the existence of the crime object of study and research. While it is true that there are procedures in one or another way guarantee the prevention and punishment of the perpetrators of such crimes, this has not been enough, being necessary to establish the procedure that currently sets the Code of Criminal Integral to provide proper prevention, punishment, support and subsequent restoration of the rights of the victim.